Ingratitude in Science: An Essay [In Bulgarian] - D. Klissurski (University of Sofia, 2015)
This essay is offered for publication by prof. Dimiter Klissurski, actual member of the Bulgarian Academy of Sciences. The theme of the essay is "ingratitude in science" - a phenomenon of importance to the scientific research community atmosphere. The essay is a contribution to the psychology of scientists.